2008
DOI: 10.1149/1.2987693
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nanostructured and Palladium Promoted (La,Sr)MnO[sub 3]-Based Cathodes for Intermediate-Temperature SOFCs

Abstract: Nanostructured and palladium-promoted Sr-doped LaMnO 3 ͑LSM͒-based cathodes are developed via solution impregnation for intermediate-temperature solid oxide fuel cells ͑IT-SOFCs͒. Both the nanostructured and Pd-promoted LSM-based cathodes show significantly improved electrochemical performance compared to the conventional LSM/Y 2 O 3 -doped ZrO 2 YSZ composite cathode, with electrode polarization resistances of 1.5 and 0.9 ⍀ cm 2 at 600°C, respectively, in contrast to 70 ⍀ cm 2 obtained from the conventional L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…The results show that at 800 • C palladium primarily exists in the form of PdO. This is consistent with the observations that the impregnated palladium mainly exists as PdO in the case of Pdimpregnated LSM/YSZ composite cathode calcined at 750 • C [28]. As the temperature increased to 900 • C, metallic palladium species is dominant, however a trace of PdO is also observed.…”
Section: Effect Of Pdo Catalyst Loadingsupporting
confidence: 89%
“…The results show that at 800 • C palladium primarily exists in the form of PdO. This is consistent with the observations that the impregnated palladium mainly exists as PdO in the case of Pdimpregnated LSM/YSZ composite cathode calcined at 750 • C [28]. As the temperature increased to 900 • C, metallic palladium species is dominant, however a trace of PdO is also observed.…”
Section: Effect Of Pdo Catalyst Loadingsupporting
confidence: 89%
“…Also, compared with the conventional LSM-YSZ composite cathode, the Pd-promoted LSM-based cathodes showed significantly improved electrochemical performance with an electrode polarisation resistance of 0.9 X cm 2 at 600°C, which is in contrast to 70 X cm 2 for the conventional LSM-YSZ cathode [14]. However, a significant growth of Pd nanoparticles was observed at 800°C and as such the stability of nanostructured electrodes by impregnation is still a major concern [15].…”
Section: Introductionmentioning
confidence: 99%
“…The results also indicate that the electrocatalytic activity of PdO for the O 2 reduction reaction is higher than that of Co 2 MnO 4 spinel phase. The significant performance enhancement with the impregnation of PdO nanoparticles has also been observed on La 0.8 Sr 0.2 MnO 3 cathode [34], La 0.8 Sr 0.2 Co 0.5 Fe 0.5 O 3 cathode [40], Pd + YSZ cathode [44]. The R E value of ∼0.13 cm 2 for the O 2 reduction reaction on PdO-infiltrated LCCM at 800 • C is comparable to ∼0.4 cm 2 at 800 • C reported on GDC-impregnated LCCM cathode [28].…”
Section: Effect Of Infiltration On the O 2 Reduction Reaction On Lccmmentioning
confidence: 59%
“…Solution infiltration is very attractive in the development of nano-structured electrodes that combine the catalytic and electrochemical active phase with the structural rigidity of porous scaffold for IT-SOFCs [31][32][33][34]. It has been shown that the electrocatalytic activity of cathodes for IT-SOFCs can be significantly improved by infiltrating wide range of catalytic active nanoparticles, such as GDC [35,36], La 0.6 Sr 0.4 CoO 3 [37,38], Pd [39,40], (Ba,Sr)(Co,Fe)O 3−ı [41], Sm 0.6 Sr 0.4 CoO 3 [42], and Y 0.5 Bi 1.5 O 3 [43].…”
Section: Introductionmentioning
confidence: 99%